Lamiaceae as Feed Additives in Fish Aquaculture - Graziella Orso; Roberta Imperatore; Elena Coccia; Ghasem Ashouri; Marina Paolucci (Fishes, 2022)
The growing demand for high-quality food has induced a rapid expansion of the aquaculture sector. On the other hand, this sector has to overcome numerous challenges and problems triggered by the adoption of intensive farming systems, such as stress and high susceptibility to diseases. The improper use of chemicals and antibiotics has led to the development of antibiotic resistance in fish, with consequent health risks for consumers. Natural additives are increasingly used in aquaculture and, among these, medicinal plants are constantly under investigation as safe and environmentally friendly alternatives to chemicals. Great attention has been paid to Lamiaceae plants as feed additives capable of enhancing the growth performance, immune system, and antioxidant status of farmed fish. The aim of this review is to provide an updated picture of the employment of the Lamiaceae species (oregano, rosemary, sage, thyme, and mint) to enhance farmed fish health. The benefits of oregano, rosemary, sage, thyme, and mint feed supplementation on growth performance, immune system, antioxidant status, hemato-biochemical parameters, and resistance to stress, parasites, and bacteria have been described, highlighting weaknesses and drawbacks and proposing possible implementations.